From discard ban to exemption: How can gear technology help reduce catches of undersized Nephrops and hake in the Bay of Biscay trawling fleet?. (15th January 2017) - Vogel, Camille; Kopp, Dorothée; Méhault, Sonia
Abstract: On January 1st, 2016, the French mixed Nephrops and hake fishery of the Grande Vasière, an area located in the Bay of Biscay, fell under the discard ban implemented as part of the new European Common Fisheries Policy. The fleet records historically high levels of discard despite numerous gear selectivity studies. Together with high discards survival, new technological solutions to minimize catches of undersized individuals could justify local exemptions from the discard ban. Our study focuses on the effects of two selective devices, a square mesh cylinder (SMC) and a grid, on the escapement of undersized individuals and discard reduction. Relative catch probability of the modified gear compared with the traditional gear was modelled using the catch comparison method. Potential losses from the commercial fraction of the catch were taken into account to assess their influence on the economic viability of fishing with the modified gears. The two devices had similar effects on undersized Nephrops escapement and on discard reduction, with median values of 26.5% and 23.6% for the SMC and of 30.4% and 21.4% for the grid, respectively. Only the grid was efficient for undersized hake, recording median values of escapement and discard reduction equal to 25.0% and 20.6%, respectively. Some loss from the commercial fraction of the catch was to be expected with both devices, which could be compensated for in the long term by the contribution of undersized individuals to the stock biomass. Our results support the use of selective gears technology as part of an integrated framework including control and management measures to mitigate the effect of the discard ban both for fishers and for the ecosystem. Further work is needed to quantify the effect of additional escapement from the gear on stock dynamics. Highlights: A square mesh cylinder and a grid were tested to reduce Nephrops and hake discards. Both devices were efficient at letting Nephrops <30 mm cephalothoracic length escape. Only the grid allowed hake <23 cm total length to escape. Commercial losses may be compensated for in the long term by improved stock dynamics.